2022
DOI: 10.1111/tbed.14509
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cross‐regional spread and evolution of equine influenza H3N8 at US and global scales using Bayesian phylogeography based on balanced subsampling

Abstract: Equine influenza virus (EIV) is a highly contagious pathogen of equids, and a wellknown burden in global equine health. EIV H3N8 variants seasonally emerged and resulted in EIV outbreaks in the United States and worldwide. The present study evaluated the pattern of cross-regional EIV H3N8 spread and evolutionary characteristics at US and global scales using Bayesian phylogeography with balanced subsampling based on regional horse population size. A total of 297 haemagglutinin (HA) sequences of global EIV H3N8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The overall clade structure reveals an apparent US-based continuous circulation that seeds multiple international transfers and outbreaks in different regions of the world (Figure 4). Some of these historical transfers have been reported and analyzed previously and confirmed here (18,(67)(68)(69)(70)(71). Our Bayesian demographic analysis of the FC1 HA1 data set (Figure S8) also shows that the effective population size largely mirrors the full-length genome data set, yet with more points of transition and changes in diversity, some of which are likely revealed by the increased sampling resolution (Figure S2B).…”
Section: Only Circulated In the Unitedsupporting
confidence: 83%
See 2 more Smart Citations
“…The overall clade structure reveals an apparent US-based continuous circulation that seeds multiple international transfers and outbreaks in different regions of the world (Figure 4). Some of these historical transfers have been reported and analyzed previously and confirmed here (18,(67)(68)(69)(70)(71). Our Bayesian demographic analysis of the FC1 HA1 data set (Figure S8) also shows that the effective population size largely mirrors the full-length genome data set, yet with more points of transition and changes in diversity, some of which are likely revealed by the increased sampling resolution (Figure S2B).…”
Section: Only Circulated In the Unitedsupporting
confidence: 83%
“…Yet we see continued FC1 infections in the United States between 2020 and 2022, and a potential inter-relatedness between US and European samples in that time, suggesting a potential return to the norm. Overall, it appears that the FC1 lineage of EIV is maintained in the horse population of the United States, and that provides viruses causing outbreaks in other regions of the world (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, we see continued FC1 infections in the USA between 2020 and 2022, and a potential inter-relatedness between US and European samples in that time, suggesting a potential return to the norm. Overall, it appears that the FC1 lineage of EIV is maintained in the horse population of the USA, and that provides viruses causing outbreaks in other regions of the world ( Lee et al. 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of 9.3% was reported in horses with acute respiratory clinical signs in a study conducted from 2010 to 2013 [ 50 ], and recently, a rt-qPCR frequency of 6,8% was reported in a voluntary sampling of 10,296 equids with acute onset of fever and/or respiratory signs for rostral nasal secretions in the country between 2008 and 2021 [ 83 ]. Phylogenetic analyses of EIV H3N8 strains from 2012 to 2017 based on the HA gene have shown that H3N8 strains from the US underwent antigenic drift and fixed multiple substitutions accumulated in the HA gene [ 84 ] and that the H3N8 FC1 North American lineage was the major source of globally dominant EIV variants and spread to other global regions [ 85 ].…”
Section: Studies On Eiv Occurrence and Reported Outbreaksmentioning
confidence: 99%